Design and development of catapult based tennis ball launcher / Muhammad Faris Mohd Razali - Mohd Razali, Muhammad Faris (2022)
The first idea to design and fabricate a projectile motion. In this project, figured out the product based on the projectile motion. This includes information on the projectile motion design, which required the time data in the flight to projectile motion experiment. Various procedures, such as idea design, designing, and fabrication process, are involved by the end of this project. After the projectile launcher has been assembled, it is tested to provide flight data, which is then solved using the projectile motion analysis equation. From there the projectile motion experiment and the objective for experiment is succeed. Overall, this project can provide new ideas and motivation for conducting various types of instruments or machine, as well as training the capacity to operate under pressure and soft skills ability such as time management.